Programming PHP - Lerdorf, Rasmus (O'Reilly Media, 2006)
In 'Programming PHP', Rasmus Lerdorf provides a comprehensive guide to this scripting language. Topics covered include forms, objects, processing, sessions, databases, graphics, standard extensions, and a detailed reference to built-in functions.